2017
DOI: 10.1111/bju.13874
|View full text |Cite
|
Sign up to set email alerts
|

Understanding pain and coping in women with interstitial cystitis/bladder pain syndrome

Abstract: The results clarify the complex and unique process of self-regulation in women with IC/BPS, implicating cognitive and coping targets, and highlighting emotional regulation. This knowledge should help clinicians understand and manage these patients' distress and disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…IC symptoms mainly manifest as pain . In addition to suprapubic or lower abdominal pain, patients with urinary frequency, nocturia, urinary urgency, incomplete bladder voiding, and dyspareunia often are considerably affected, with symptom severity being irregular, intermittent, recurrent, or persistent .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…IC symptoms mainly manifest as pain . In addition to suprapubic or lower abdominal pain, patients with urinary frequency, nocturia, urinary urgency, incomplete bladder voiding, and dyspareunia often are considerably affected, with symptom severity being irregular, intermittent, recurrent, or persistent .…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that IC/BPS was associated with not only increased risks of subsequent health care‐seeking behavior for anxiety, depression, and insomnia but also with a higher degree of depressive and anxiety symptoms compared with controls . The disease affects the conscious status of IC/BPS patients, as symptoms can cause feelings of anxiety and apprehension about going outside, sleep disturbance due to voiding frequency and nocturia, and sexual intimacy . However, many doctors do not focus on IC/BPS patients' mental illness, subjecting them to numerous ineffective trial, and error treatments that typically cause more depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations